THE ANALYSES OF BEEBREAD PRODUCTION TECHNIQUES - П´ясківський, В. М.; Вербельчук, С. П.; Вербельчук, Т. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The apiculture of Ukraine is in the process of dynamic development. Honey production is increased; the other kinds of production techniques are implemented; the export expansion is observed. Beebread is unique bee product. However; the existing techniques of its production are extremely labor-intensive and slightly mechanized. EU integration has required the producers of beekeeping products follow the innovative techniques requirements; quality and purity requirements. It is necessary to create the standard and safety system for various kinds of products. The article focuses on the methods based on the generalization of beebread nature indices; their importance for bees and human; on the existing production techniques of the product and actually developed experimental research. The research is based on the set of rules and procedures which contain a number of techniques; and their application make it possible to systemize the previous research; to identify beebread production efficiency. Such methods include empirical and theoretical method; the method of systematization; experimental; logical; economical and statistical methods. The description of the main existing beebread techniques has been analyzed by the authors. The article considers the nature of the pollen; its sipping; preservation and use by the bees; microbiological processes of pollen load conversion into preserved product – beebread. The possible ways of production intensification have been offered. The efficiency of beebread production with the help of gravure spatula and with the help of unbent paper clip has been compared during the research. In spite of the simplicity; the given methods and tools are current for the apiaries of different size. Beebread production with the help of shoulder engraving was 6;5% higher in efficiency. The quality; marketability and price of the products are higher. The research recommends to apply the shoulder engraving on farms with manually small-scale beebread production. The work needs research continuation relative to morphological content; physical; chemical and biochemical indices according to the programme of all-Ukrainian project “Biodiversity of melliferous and pollen herbs in Ukraine – 2016” which is included into the international project Agro Bio Net